Commoning the Established Order of Property: Reclaiming Fishing Commons in Mumbai. (November 2020) - Kamath, Lalitha; Dubey, Gopal
This article narrates how a fisherfolk community comprising original inhabitants of Mumbai has been spatially squeezed and choked by surrounding urban developments, compelling them to turn away from their customary livelihoods and ways of living. The community resists this through a political project of indigenous reclaiming. The project is material in nature—focused on reclaiming alienated lands—but also imaginative—reasserting a newly imagined, albeit contested, identity as a fishing community founded on repurposing its fishing commons and reconfiguring the dominant notion of property as private. Using the lens of boundaries allows us to understand the closures and opportunities presented by these complex urban transformations. Overall, the fishers' reclamation is directed at redefining, contesting, blurring and 'commoning' the established ordering boundary of private property that erases their customary claims—their remembered boundary spans not just the village settlement but also the land–sea commons—and is seen as unjust.